Strong convergence algorithm for the split problem of variational inclusions, split generalized equilibrium problem and fixed point problem - Husain, Shamshad; Asad, Mohd; Khairoowala, Mubashshir (Armenian Journal of Mathematics, 2021)
The purpose of this paper is to recommend an iterative scheme to approximate a common element of the solution sets of the split problem of variational inclusions, split generalized equilibrium problem and fixed point problem for non-expansive mappings. We prove that the sequences generated by the recommended iterative scheme strongly converge to a common element of solution sets of stated split problems. In the end, we provide a numerical example to support and justify our main result. The result studied in this paper generalizes and extends some widely recognized results in this direction.